Closing Speech by Brig. Gen. Dato’ Prof. Dr. Kamarudin Hussin the Vice Chancellor of UniMAP for Closing Ceremony 11th IMT - GT Varsity Carnival - Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Dewan 2020 Kangar, Perlis.